Effect of power distribution on the weld quality during hybrid laser welding of an Al–Mg alloy. (October 2015) - Leo, P.; Renna, G.; Casalino, G.; Olabi, A.G.
Abstract: This paper treats of the analysis of the effect of arc and laser powers on the quality of the arc assisted fiber laser welding of an Al–Mg alloy in the butt configuration. Grain size, weld geometry defects, porosity, and magnesium loss were measured. Magnesium content of the fused zone decreased as the laser power increased while the porosity increased with laser power. Microhardness profiles and tensile properties were explained on the basis of the joint microstructure and defects and related to the power distribution. The porosity level and Mg content in the fused zone affected both tensile strength and ductility. The power distribution that stabilized the welding process and minimize the weld porosity was defined. Highlights: Study of the hybrid fiber laser welding soundness of Al‐MgAl–Mg weld. Effect of the arc and laser power distribution on the weld quality. Emphasis on metallurgy and mechanical properties of the weld. Reduction of Al–Mg laser welding porosity. Determination of the power distribution that stabilized the welding process.